Increasing the acetification rate of Acetobacter aceti adsorbed on luffa sponge using recycle of incremental oxygenated medium - Krusong, Warawut; Vichitraka, Assanee; Sriphochanart, Wiramsri; Pornpukdeewattana, Soisuda (My University, 2020)
Speeding up the production of vinegar from rice wine by acetification, using a packed-bed bioreactor with a luffa sponge matrix (LSM) as adsorption carrier of acetic acid bacteria (AAB), and the effect of oxygenation of the recycled medium were investigated. The 0.06 L/min recycle of medium resulted in a high oxygen-transfer coefficient, while optimal dissolved oxygen (DO) of the medium maximized planktonic AAB cell growth with no contamination due to high acid in an external reservoir without LSM. The highest acetification rate (ETA) of 2.857 ± 0.1 g/L/day was achieved with DO 3.5–4.5 ppm at 35 ± 1 °C. To increase ETA, the optimized oxygenated medium was externally supplied and recycled at the ratio of 0.1. Therefore, acetification was conducted in both the bioreactor and reservoir resulting in an increased ETA (6 ± 0.2 g/L/day). This also aligned with the highest system AAB biomass (confirmed by scanning electron microscopy). Under the recycled oxygenated medium supply consistently high biotransformation yields (average 77.3%) were observed over nine sequential cycles. Meanwhile, an average ETA of 6.3 ± 0.2 g/L/day was obtained. This method can have practical applications in improving the efficiency and speeding up small-scale vinegar production.
Keywords: Green process; Loofa sponge matrices; Oxygenation; Packed-bed bioreactor; Recycled medium